Penilaian Keselamatan Kontruksi pada Pekerjaan Tunnelling dengan Memanfaatkan Foto Kontruksi Proyek Pembangunan Bendungan Manikin - Koko Heru Satmoko; Achmad Djunaedi; Fitri Nugraheni (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Tunneling construction is important to get more attention because considering the magnitude of the risks from this work such as the instability of the carrying capacity of the soil around the construction which can cause collapse during dredging or installation of tunneling walls, or and other problems such as lack of oxygen intake for workers who are carrying out tunneling excavations , the presence of toxic and flammable gases, or falling objects that can result in minor accidents or even death. The purpose of this study is to make a visual assessment through certain media (photos/videos) that can be done quickly regarding the existing conditions of the environment/work, whether the work carried out meets work safety standards, work safety regulations and so on. Rapid assessment can assume that what happened in the field at that time was a reflection of previous work. From the results of the study there were 58 variables which were divided into 4 main variables which were assessed based on the WBS and 26 photos of the environment of the Manikin Dam Tunneling development project taken from several sides. Calculations were made using the results of data from 6 informants, resulting in a P(H | Ecomb) value of 0.932 or a probability of 93.2%, which means that the tunnel work according to the 6 informants was carried out safely. The final value obtained from the analysis is almost close to 1 and all the results of the analysis from the 6 informants are more than 67%.